PHENOMENON OF COUNTERCULTURE IN MODERN SOCIETY - Новак, Т. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the phenomenon of counterculture is probed through a prism concretely historical events (on the example of mass people-student motions of leading occident of the second half of the XX century).